P390The modulation of cardiac muscle Ca2+-sensitivity by PKA phosphorylation can be uncoupled by EMD57033 and re-coupled by EGCG. (15th July 2014) - Messer, A E; Papadaki, M; Vikhorev, P; Marston, S B
Abstract: Hypertrophic cardiomyopathy (HCM)-causing mutations in sarcomeric proteins have been proposed to increase myofilament Ca2+-sensitivity. Dilated cardiomyopathy (DCM)-causing mutations may decrease myofilament Ca2+-sensitivity but recently some mutations have been found that show an unchanged Ca2+-sensitivity whilst some even showed an increase in Ca2+-sensitivity. However, a common feature of most DCM and several HCM-causing mutations is the uncoupling of the phosphorylation of Ser 22 and 23 of cardiac troponin I from the change in Ca2+-sensitivity. We studied the effects of small molecules that bind to troponin C to modulate Ca2+-sensitivity using single thin filaments containing human cardiac troponin moving on skeletal myosin in the in vitro motility assay. EMD57033 is a Ca2+-sensitiser and causes a dose dependent increase in Ca2+-sensitivity (optimum at 30μM). EMD57033 increased Ca2+-sensitivity in wild-type, in DCM mutations (TPM1 E40K and E54K) and in troponin from myectomy samples (from patients with hypertrophic obstructive cardiomyopathy). In addition, in wild-type, Ca2+-sensitivity becomes independent of troponin I phosphorylation, this uncoupling by EMD57033 mimics the effect of HCM mutations in this system. Epigallocatechin 3-Gallate (EGCG) is a Ca2+-desensitiser, 100μM reduces Ca2+-sensitivity of native human thin filaments by 1.5-fold. EGCG also decreased Ca2+-sensitivity in thin filaments with DCM mutations (TPM1 E40K and E54K) HCM mutations (TNNT2 K280N) and in troponin from myectomy samples. Uniquely, EGCG also restored the phosphorylation dependence of Ca2+-sensitivity to thin filaments containing tropomyosin DCM mutations or myectomy samples where the Ca2+-sensitivity is normally uncoupled. For thin filaments with the tropomyosin E40K mutation, Ca2+-sensitivity of phosphorylated (P) and unphosphorylated (unP) troponin is the same (EC50 0.261μM and 0.252μM respectively) whilst in the presence of EGCG, Ca2+-sensitivity dependence on phosphorylation is restored (EC50 P = 0.324μM, unP = 0.104μM). The same pattern was observed with four other DCM mutations, two HCM mutations and also in troponin from myectomy samples that are usually uncoupled. The Ca2+-sensitivity and recoupling effects were also seen in contracting myofibrils. Propranolol treatment dephosphorylates myofibrils with a corresponding increase in Ca2+-sensitivity. However, with the ACTC DCM mutation E361G, there was no difference in Ca2+-sensitivity. When EGCG was added, the Ca2+-sensitivity difference was restored. Thus, EGCG potentially can reverse the effect of mutations that cause DCM.